Jean Cruveilhier (1791-1874), a Predecessor of Evidence-Based Medicine - Luis-Alfonso; Talía Fuentes-Redondo; José-Luis; Rafael Romero-Reverón (MDPI AG, 2023)
This article focuses on Jean Cruveilhier and particularly on his book Anatomie descriptive, which was a great success during the author's lifetime. (Notwithstanding this, it is pertinent to point out that the five editions of Anatomie descriptive were surpassed in number by others of the Cruveilhier's creations, such as Anatomie pathologique and Traité d'Anatomie pathologique.) Unlike other texts of the time and later, Anatomie descriptive presents the anatomy of the human body in a way that can be applied both by students and medical professionals. The objectives of Anatomie descriptive were to make understand how the functions of an organ can be inferred from its structure, and to encourage students and professionals to investigate the anatomical origin of health and disease phenomena. Depending on which sections of the book, the parts of the body were described with morphological, topographic or functional criteria. Many of Cruveilhier's contributions influenced anatomical eponymy and keep today's Terminologia Anatomica alive. All of this has made consider Jean Cruveilhier the most outstanding anatomist in France of the first half of the nineteenth century. Due to the scientific rigor Cruveilhier always applied and asked to be applied in the investigation of the anatomic changes linked to pathological processes, he could certainly be considered a predecessor of the objectivity sought by evidence-based medicine.